DIGITAL PLATFORMS AND THE DIGITISATION OF GOVERNMENT SURVEILLANCE - Ó Fathaigh, Ronan; Möller, Judith; Bellanova, Rocco (AoIR Selected Papers of Internet Research, 2021)
In Europe today, digital platforms, such as Facebook, Twitter and YouTube, provide essential means for millions of people to express themselves, engage in public debate, and organise politically (Poell & van Dijck, 2018). Crucially, governments are leveraging the power of platforms to impose new forms of restrictions on free expression, and engage in surveillance of individuals and online activism. This has profound implications for the rights to freedom of expression, privacy, and data protection. Further, platforms that once refused to cooperate with governments in identifying users responsible for disseminating allegedly illegal or harmful content are now expanding cooperation with authorities, including sharing data about users flagged by law enforcement and other authorities. As civil society organisations warn, this trend is contributing to ‘invasive and unlawful digital surveillance’ (Amnesty International, 2019, p. 24). This paper examines how European governments are leveraging the power of digital platforms to engage in government surveillance online, and assesses the compatibility of these measures with European human rights law. The paper applies a unique interdisciplinary perspective, bringing together law, political communication and surveillance studies. First, the paper examines how platforms’ algorithmic systems shape (and limit) information dissemination. The paper then critically analyses government-platform initiatives that exist to surveil citizens and gather information, including new measures under the EU’s proposed Digital Services Act. Third, it assesses how these measures comply with freedom of expression and the right to privacy, and concludes with recommendations on remedying problematic elements of the role platforms play in digitisation of government surveillance.